Restoring global leadership: US foreign policy under Barack Obama - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2008)
In the last four decades, no incumbent US president has faced such a formidable array of problems and challenges as Barack Obama does today: two wars being fought simultaneously, nuclear-armed Pakistan in a state of precarious stability, Iran possibly soon to be developing its own nuclear weapons program, relations with Russia in a difficult phase. And all that at a time when the scope of options for foreign policy are severely constrained by the economic and budgetary consequences of the financial crisis. In this context, the goal on which Barack Obama has set his sights looks extremely ambitious: that of renewing American leadership in the world. What understanding of the US role underlies this project, and how will this vision of restored American leadership shape foreign policy?
Keywords: 320